Hubungan Durasi Tidur dengan Agresivitas Mahasiswa Program Studi Pendidikan Dokter Universitas Sam Ratulangi - Purba, Revand; Sinolungan, Jehosua S. V.; David, Lydia E. V. (Medical Scope Journal, 2025)
Abstract: Sleep issues can impact the emotional well-being and behavior of students, particularly in medical education environments. Factors such as stress, physical violence, and increased academic workload may contribute to aggressive behavior among medical students. This study aimed to evaluate the relationship between sleep duration and the level of aggression among third semester students of Medical Education Program Universitas Sam Ratulangi. This was an analytical study with a cross-sectional design. Primary data were collected using the Buss Perry Aggression Questionnaire and sleep duration was categorized based on the recommendation of the National Sleep Foundation. The results showed that the majority of students had not-recommended sleep duration (45.1%), and they exhibited a moderate level of aggression (51.8%). The Spearman test for the relationship between sleep duration and the level of aggression showed a correlation coefficient of 0.095 with a p-value of 0.185. In conclusion, there is no significant relationship between sleep duration and the level of aggression among third semester students of Medical Education Program, Universitas Sam Ratulangi. Keywords: sleep duration; aggression; medical students   Abstrak: Masalah tidur dapat memengaruhi kesejahteraan emosional dan perilaku mahasiswa, khususnya dalam lingkungan pendidikan kedokteran. Faktor-faktor seperti stres, kekerasan fisik, dan beban akademik yang bertambah dapat berkontribusi pada perilaku agresif mahasiswa kedokteran. Penelitian ini bertujuan untuk mengetahui hubungan antara durasi tidur dengan agresivitas pada mahasiswa semester 3Program Studi Pendidikan Dokter Universitas Sam Ratulangi. Jenis penelitian ialah analitik korelasi dengan desain potong lintang. Data primer dikumpulkan menggunakan Buss Perry Aggression Questionnaire dan durasi tidur dikategorikan menurut National Sleep Foundation. Hasil penelitian mendapatkan bahwa sebagian besar mahasiswa semester 3 Prodi Pendidikan Dokter Universitas Sam Ratulangi tidur dalam durasi yang tidak direkomendasikan (45,1%) dan memiliki tingkat agresivitas sedang (51,8%). Hasil uji Spearman terhadap hubungan antara durasi tidur dan tingkat agresivitas mendapatkan nilai koefisien korelasi sebesar 0,095 dan nilai signifikansi p=0,185. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara durasi tidur dan tingkat agresivitas pada mahasiswa semester 3 Prodi Pendidikan Dokter Universitas Sam Ratulangi. Kata kunci: durasi tidur; agresivitas; mahasiswa kedokteran